INFLUENCE OF LENGTH OF SERVICE ON WORKERS' ATTITUDE TOWARDS OCCUPATIONAL HAZARD. - UGWU, DOROTHY IFEYlNWA, UGWU, DOROTHY IFEYlNWA (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
The study examined the attitude of workers towards occupational hazards and the attitude of long and short serving workers towards occupational hazards in Anambra Motor Manufacturing Company (ANAMCO), Enugu, Nigeria. One null hypothesis was tested at 0.05 level of significants. The population for the study consisted of 521 workers of ANAMCO. The instrument usedfor the study was Attitude of WorkersRegarding Occupational Hazards Questionnaire (AWROHQ). This was designed by the researcher Stratified sampling and simplerandom sampling techniques were used to draw sample for the study. Mean, standard deviation and student t-test were used for data analysis. Results revealed that worlte.~ in ANAMCO Company had favourable attitude towards their workplace hazards; long serving workers showed more favourable attitude than the short servingworkers. However, the result revealed no significant difference in the attitiiiJe of the long and short serving workers towards their hazardous work environment. In view of this, it was recommended, among others, that management should show strong and true commitment to occupational health and safety so that all workers, irrespective of length of service, will improve their attitude regarding safety in their work environment.